ANALISIS KEPUASAN PENGGUNA WEBSITE DINAS KOMUNIKASI DAN INFORMATIKA BANTUL MENGGUNAKAN METODE WEBQUAL 4.0 - Ahmad Qois Amrullah, Ahmad Qois Amrullah; Rochmadi, Tri; Ratnasari, Asti; Wicaksono, Yanuar (ITB Ahmad Dahlan Jakarta, 2024)
The development of information technology plays an important role in providing digital services, including government websites. The Bantul Communication and Informatics Service manages the website as a means of disseminating news, public information, announcements and videos of activities. However, in 2019, this website service was not optimal in providing information. Since 2022, system and appearance improvements have been made to improve service quality. This research aims to analyze the level of satisfaction of users of the Bantul Communication and Informatics Service website using the WebQual 4.0 method, which includes the variables ease of use, information quality, service interaction and user satisfaction. Data were analyzed using multiple linear regression and classic assumption tests with SPSS version 25, preceded by validity and reliability tests on 30 respondents from Bantul. Using a non-probability sampling technique, data was collected through questionnaires from 100 respondents from Bantul residents, 30 September - 7 October 2024. The research results showed that the WebQual 4.0 method was effective in assessing website quality, with two of the three hypotheses accepted. Regression analysis revealed a coefficient of determination (R Square) of 81.5%, indicating that the variables ease of use, information quality and service interaction influenced user satisfaction by 81.5%, while 18.5% was influenced by other factors. The T test shows that ease of use is not significant on satisfaction, but the quality of information and service interaction has a significant effect. The F test shows that the three variables have a significant effect simultaneously on user satisfaction.